2015
DOI: 10.4103/2249-4472.155193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrathecal magnesium and fentanyl as adjuvants to hyperbaric bupivacaine in preeclamptic parturients undergoing elective cesarean sections

Abstract: A B S T R A C TAims: The aim of this study was to evaluate the onset, duration of sensory and motor block, hemodynamic effects (if any), duration and quality of postoperative analgesia, and adverse effects of magnesium or fentanyl given intrathecally with hyperbaric 0.5% bupivacaine in patients with mild preeclampsia undergoing elective caesarean sections. Materials and Methods: A total of 60 women with mild preeclampsia undergoing elective cesarean section were included in a prospective, double-blind, control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…This study agreed with Arora, et al ( 2015) (7) which found that the time to reach maximum block height (5.3 ± 0.5 min vs. 8.7 ± 0.5 min) and the onset of motor block (5 ± 1 min vs. 6 ± 1 min) were significantly slower in Group M than in the Group F.…”
Section: Ashraf S; Et Al… -126-supporting
confidence: 93%
See 4 more Smart Citations
“…This study agreed with Arora, et al ( 2015) (7) which found that the time to reach maximum block height (5.3 ± 0.5 min vs. 8.7 ± 0.5 min) and the onset of motor block (5 ± 1 min vs. 6 ± 1 min) were significantly slower in Group M than in the Group F.…”
Section: Ashraf S; Et Al… -126-supporting
confidence: 93%
“…This result agreed with Arora, et al (2015) (7) who found that there was no significant differences between both groups in the maximum level of sensory block it was T 4-6 in group M and T 4-6 in group F. Also Katiyar, et al (2015) (15) had the same results.…”
Section: Ashraf S; Et Al… -126-supporting
confidence: 89%
See 3 more Smart Citations